Effect of continuous and intermittent exercises on oxidised HDL and LDL lipids in runners - Välimäki, I. A.; Vuorimaa, T.; Ahotupa, M.; Vasankari, T. (International Journal of Sports Medicine, 2016)
We studied the effects of different types of exercises on the concentrations of oxidised HDL (oxHDLlipids) and LDL lipids (oxLDLlipids), serum lipids, antioxidant potential, paraoxonase and malondialdehyde in endurance runners by performing both a 40-min continuous run (velocity corresponding to 80% VO2max) and a 40-min intermittent run (2-min run, velocity corresponding to 100% VO2max, and 2-min rest) using a treadmill. Blood samples were taken before exercise, after 20 and 40?min of exercise, and 15 and 90 min after the end of exercise. The concentrations of oxLDLlipids remained unchanged during the running tests, but after a 90-min recovery the concentrations decreased by 4% (P<0.05) for the intermittent run and by 16% (P<0.01) for the continuous run. The acute effect of the intermittent and continuous run increased the concentrations of oxHDLlipids by 26 and 25%, respectively (P<0.001 for both). Interestingly, oxHDLlipids did not increase after the first half of the run in middle-distance runners during the intermittent run, and a similar phenomenon was seen in marathon runners during the continuous run. These results may indicate that acute physical exercise increases the transport of lipid oxidation products by HDL, although a different training history or genetic background may alter these acute responses.